Andragogy: Successes and Failures in Teacher Training in Ict - Morales Pacavita, Olga Sofía; Leguizamón González, Myriam Cecilia (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This research covers an interpretation of the successes and failures of the adult learning theory (andragogy) in teacher training in the use of ICT’s for developing technological skills. A case study was made using participant observation as the main method for data collection. Likewise, a parallel between andragogy and the reality studied was made evidencing the fact that qualifications fall far short of teacher learning needs, the low motivation generated in this spaces and the distance between the interests of the entities seeking to qualify the teachers and the people qualified.